â€œAnalisis Pengaruh Kompetensi Dan Loyalitas Karyawan Terhadap Promosi Jabatan Pada PT. Bank Pembangunan Daerah Jawa Timur Tbk. ( Bank Jatim ) Cab. Pasuruan â€ (Deskripsi penelitian di Bank Jatim Cab. Pasuruan) - Wicaksono, Daniel Putro (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2014)
There are fiveÂ sources of production factors in the company, but the only factor that showed a potential advantage is the human resource. To empower and improve the quality of human resources in order to increase production company one of them with promotion.Â In bankingÂ theÂ human resource production factors directly affectÂ toÂ the performance of the company therefore the company should be well thoughtÂ of his promotion system . BankÂ JatimÂ has a good promotion programsÂ systemÂ Â Â include staff development program (SDP), Manager Development Program (MDP) and Exsecutive Development Program (EDP). The promotion system has a requirement of at least two years of work and successfully passed on the test. This study uses multiple regression analysis with SPSS version 21 . Methods of data collection using questionnaires for collecting data on employee career on Bank Jatim Pasuruanâ€™s Branch Office. ThisÂ study aims to find out the influence of the competence and loyalty of employees towards promotion. From the results of this study found that the competence and loyalty of employees affect significantly and positively to the promotion. The Employee loyaltyÂ hasÂ the dominant influence on promotion at Bank Jatim Branch Office Pasuruan . Keywords: competence , loyalty and promotion